(untitled) (Research, Society and Development, 2020)
The work is the result of the extension project “Transfer of technology through training and technical assistance for creators of tambaqui, Colossomamacropomum, in the Marajóarchipelago/PA”. This article discusses the use of rural extension methodologies applied to family fish farming, drawing a parallel between theory and practice based on concepts and experiences. The methodological practices were carried out by students and teachers from the Federal Institute of Education, Science and Technology of Pará (IFPA) CampusBreves, in the city of Curralinho (Marajó - Brazil). The duration of the project was from August 2019 to March 2020. This descriptive study, with a qualitative approach, is configured as an experience report. In this sense, here are presented some, among many, methodologies that can assist in data collection for aquaculture, such as: meeting; contact; visit; cross walk; poster; folder; radio; seminar; course; lecture; interviews; workshop; model; problem tree; reality/desire; SWOT analysis (Strengths, Opportunities, Weaknesses and Threats); production and commercialization flows. In conclusion, the methodologies used in this project were presented as excellent tools in the technical assistance and rural extension process in Marajó aquaculture.